A multimethod approach to inform epikarst drip discharge modelling: Implications for palaeo‐climate reconstruction. Issue 26 (23rd November 2017) - Campbell, Micheline; Callow, John Nikolaus; McGrath, Gavan; McGowan, Hamish
Abstract: Resolving the hydrological processes that form speleothems and the palaeo‐climate archives that they contain is difficult. Typical approaches to hydrological investigation are not suited to karst landscapes, geophysics are seldom applied, drip monitoring and modelling have limitations, and ignoring potential hydrological impacts can result in a proxy record that does not reflect the external environment. We aim to understand the processes and controls that have created a palaeo‐climate proxy record preserved in a speleothem (JC001) in the "Grotto of Oddities, " part of the Jersey Cave at the Yarrangobilly Caves, Australia, to infer the likely nature and resolution of this record. Electrical resistivity tomography (ERT), traditional surveying, and drip discharge monitoring (April 2013 to February 2015) were used to investigate the structure and hydrology of the epikarst overlying the Grotto of Oddities. Data collected through these methods were then used to construct a physically informed and parsimonious drip hydrology model. Geophysics showed that changes in hillslope above the Grotto of Oddities are collocated with a region of low resistivity, which forms an epikarstic reservoir acting to supply enhanced discharge to the speleothem. Drip monitoring showed hysteretic behaviour with a distinct threshold response, and a simple drip classification indicated that the speleothem associated with the drip has the potential to record palaeo‐seasonality or an annual–decadal signal. Discharge modelling indicated discharge was comprised of quick and slow flow, and that discharge is probably perennial. These multimethod results together indicate that the speleothem likely represents a palaeo‐climate record of a length and resolution unprecedented for nonglacial areas of the Southern Hemisphere and for Australia in particular and will significantly enhance current knowledge of the climate of southeast Australia. Although ERT methods have previously been applied in the karst landscape, to our knowledge, this represents the first application of these multiple methods in combination as an approach to assess the fidelity of a speleothem, based on an understanding of the hydrological processes for palaeo‐climate reconstruction.